1994
DOI: 10.1007/bf02190579
|View full text |Cite
|
Sign up to set email alerts
|

The rate of recovery following whiplash injury

Abstract: Fifty consecutive patients with soft-tissue neck injuries following rear end collisions were studied prospectively to assess their rate of recovery. Patients were seen within 5 days of the accident, after 3 months, 1 year and 2 years, and their symptoms were classified into one of four groups (A, asymptomatic; B, nuisance; C, intrusive; D, disabling). Fourteen of 15 patients (93%) who were asymptomatic after 3 months remained symptom-free after 2 years. Of 35 patients with symptoms after 3 months, 30 (86%) rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 7 publications
2
50
0
9
Order By: Relevance
“…6,9 The chance of recovery is less favourable for women and decreases with age -14% for every decade according to Harder et al 15 Longer-term (for example, after 5 years) recovery figures are comparable with the figures after 1-year follow-up. 13,16 The majority of patients in these studies reported hardly any change over the years but, if change occurs, deterioration outbalances improvement. Almost all studies available on the prognosis of whiplash are hospital based; 17 thus they are referral based and, therefore, subject to caseselection bias.…”
Section: Introductionmentioning
confidence: 96%
“…6,9 The chance of recovery is less favourable for women and decreases with age -14% for every decade according to Harder et al 15 Longer-term (for example, after 5 years) recovery figures are comparable with the figures after 1-year follow-up. 13,16 The majority of patients in these studies reported hardly any change over the years but, if change occurs, deterioration outbalances improvement. Almost all studies available on the prognosis of whiplash are hospital based; 17 thus they are referral based and, therefore, subject to caseselection bias.…”
Section: Introductionmentioning
confidence: 96%
“…This information should help the clinician make more precise diagnoses in the case of whiplash trauma patients. only 38% of the whiplash patients had recovered at their 2-year follow-up [11]. There is a consensus that most whiplash patients suffer soft tissue injuries [8,16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…7 A large proportion of patients appears to reach a final state of recovery or chronic symptoms within three months of injury. 5,8,9 The symptoms are often disproportionate to the physical signs 10 and have been shown to correlate poorly with the findings on plain radiographs, 10,11 scintigraphy 12 and MRI. 13 Partly for this reason, the syndrome has been frequently associated with psychological disease.…”
mentioning
confidence: 99%